THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE SAMSAT NIGHT PROGRAM IN INCREASING MOTOR VEHICLE TAX (PKB) REVENUE AT THE UPTD BAPENDA BINJAI - Ahmad Taufiq; Syafruddin Ritonga; Maksum Syahri Lubis (Pena Cendekia Insani, 2026)
This study aims to analyze the effectiveness of the implementation of the Samsat Night Program in increasing Motor Vehicle Tax (PKB) revenue at UPTD Bapenda Binjai and to identify the factors that hinder its implementation. The Samsat Night Program is a public service innovation that extends operating hours into the evening to provide easier access for taxpayers who are unable to fulfill their obligations during regular working hours. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the effectiveness of the Samsat Night Program, based on Duncan’s (1981) indicators goal attainment, integration, and adaptation has not yet been fully optimal. In terms of goal attainment, the program has contributed to improving service delivery and PKB revenue; however, the increase has not been significant overall due to fluctuating levels of public participation. From the integration perspective, coordination among related institutions (Bapenda, the Police, and Jasa Raharja) has functioned relatively well in the technical implementation of services. Meanwhile, from the adaptation aspect, the program has adjusted service hours to meet community needs but still faces challenges such as limited socialization, restricted service locations, and low taxpayer awareness.